Od znaku „Polski Walczącej” po hasło „FaceBóg” – rola polskiego graffiti w latach 1942–2011 - Nowak-Kluczyński, Konrad (Biuletyn Historii Wychowania, 2011)
Against the general opinion the history of graffiti goes back to the beginnings of civilization. There are numerous examples of graffiti, for instance the inscriptions hollowed with a chisel found on the ancient household artifacts or on the walls. The inscriptions had an informative function but they were also magical. The phenomenon of spray art was widespread in the 1960s and the beginning of the Polish taggers subculture was in the 1980s, although one can find street art during the Second World War. But it is usually neglected or disregarded in the Polish literature. The Anchor – the sign of “Fighting Poland”, was placed on pavements, walls, notice boards or train stops of the occupied country. It was the sign of the fight for freedom and independence. As the years passed, the Polish reality was changing and the role of graffiti also changed. Now, it expresses itself in slogans, appeals, messages, drawings, portraits or murals. The aim of the work is to show the role of the Polish graffiti between 1942 and 2011. The author analyses graffiti in a number of aspects and throughout many years. The author identifies Polish spray art with teenage rebellion, sense of humor, political engagement, commentary or the negation of reality. Moreover, the article focuses on social, psychological or urban aspects of the examined phenomenon and identifies it with widespread modern hip-hop culture.